Artificial Intelligence (AI) in Education: Survey, Trends, Challenges and Recommendations for Sub-Saharan African and Developing Countries - Bello, Oladipupo; Albaba, Babangida Abubakar (PT. Riset Press International, 2026)
The future of education is closely connected with the deployment of emerging technologies, competent manpower and efficient infrastructures. Artificial Intelligence (AI) technologies are now part of our daily lives and becoming indispensable especially for creative, innovative and productive uses. These offer new possibilities and challenges for students, educators and administrators of educational institutions and have also transformed the services rendered by educational institutions. AI in education (AIEd) is however complex task that requires human and financial resources for successful implementation. This paper surveys the literature along with the recent applications of AIEd. The associated challenges were identified in this study. Suggested recommendations to implement AI in education especially in the developing countries include development of a reliable and comprehensive policy framework, adequate provision of high-tech digital devices and infrastructures. There is a need to promote data privacy, security, transparency, accountability when AI technologies are used for solving problems in the academic environment. Policy makers, administrators, educators and students can make the best use out of educational institutions when AI technologies with a well-crafted strategic plan is integrated into every aspect of the educational landscape.